Long-Term Hepatitis B Vaccine Immunity in Ethiopian Children That Received a Pentavalent Vaccine Series: A Retrospective Cohort Study - Tinsae Alemayehu; Million Dechassa Daba; Danilo Buonsenso (MDPI AG, 2024)
Background: Chronic hepatitis B affects close to 300 million people globally with 1.5 million new infections per year. It causes the highest numbers of cirrhosis and liver cancer diagnoses each year. In children, perinatal transmission and contact with infected blood or body fluids remain the main methods of transmission. There are increasing reports of breakthrough hepatitis B infections in fully vaccinated children born to hepatitis B-negative mothers, especially in low- and middle-income countries. Our study aimed to measure the adequacy of hepatitis B surface antibody levels among children and adolescents who received three rounds of hepatitis B vaccination during infancy and delivered to hepatitis B-negative mothers in Addis Ababa, Ethiopia. Method: This was a retrospective cohort study analyzing results of paired serology tests for hepatitis B surface antibody and antigen tests performed for children aged 1-18 years from July 2022 to June 2023. All recorded data were transferred to SPSS version 29.0. The prevalence of adequate hepatitis B surface antibody levels was determined and sub-group analysis conducted using descriptive statistics, frequencies and tables. The magnitude of association between different variables and vaccine-induced hepatitis B immunity was assessed using logistic regression. Statistically significant differences were taken at p < 0.05. Results: A total of 256 children were included in the study (mean age: 7.53 years). Six children (2.3%) had breakthrough hepatitis B infections. Overall, 37 children (14.4%) were categorized as having optimal hepatitis B surface antibody levels (vaccine-induced antibody titers of >10 IU/mL), while 219 (85.6%) had low titers of <10 IU/mL. Nearly all (97.4%) of the sub-group aged 10 years and above had below-par antibody levels, with adolescents (11-18 years) being ten times more likely to have low seroprotection than those aged less than 5 years. Conclusions: Our study showed markedly low vaccine-induced hepatitis B surface antibody levels among the study population, especially adolescents. The presence of breakthrough infections may suggest a genuine lack of response and not just a mere drop in antibody titers and thus could highlight a significant public health problem in Ethiopia. Further immunologic studies and a thorough analysis of vaccine storage and administration should be conducted to inform prevention programs.